Creation of oxygen vacancies to activate WO3 for higher efficiency dye-sensitized solar cells. Issue 2 (24th November 2017) - Elbohy, Hytham; Reza, Khan Mamun; Abdulkarim, Salem; Qiao, Qiquan
Abstract : Oxygen vacancies were created to activate tungsten trioxide (WO3 ) as a highly efficient counter electrode (CE) in dye-sensitized solar cells (DSSCs). Abstract : In this work, oxygen vacancies were created to activate tungsten trioxide (WO3 ) as a highly efficient counter electrode (CE) in dye-sensitized solar cells (DSSCs). The levels of oxygen vacancies (OVs) in WO3 were finely formed and tuned by doping with different weight percentages (3, 5, and 9 wt%) of urea and annealing in a N2 environment at 470 °C. The urea doped WO3 significantly improved the electrocatalytic behaviour in the iodide–triiodide electrolyte. The effects of OVs on the catalytic performance of WO3 CEs were fully studied and understood. This improvement was attributed to the introduction of OVs into WO3, which acted as surface shallow states to facilitate electron transfer from the WO3 counter electrode to the electrolyte. At a high temperature of 470 °C, urea decomposes into the reactive H2 gas that can remove oxygen atoms from the WO3 surface and create OVs. 5 wt% urea was found to be the optimal urea concentration that led to the highest catalytic performance as evidenced by the cyclic voltammetry measurements. The 5 wt% urea doped WO3 CE-based device achieved a power conversion efficiency (PCE) of ∼10.5%, which was improved from the reference Pt CE-based device at ∼9.3% and non-active WO3 CE based cell at 3.32%. This has led to the optimal number of OVs that facilitate the charge transfer at the CE/electrolyte interface.